Airway remodeling in asthma - Roni Naning; MTS Darmawan (Paediatrica Indonesiana, 2001)
Airway remodeling is the term given to a series of structural changes characterized by chronic, irreversible airway obstruction. Structural changes in the airway wall caused by chronic inflammation of asthma. Evidence for asthma airway remodeling demonstrating an accelerated decline of lung function that cannot be completely reversed with therapy. Combination therapy produced at least as much protection against inflammation as theuse of the higher dose of the inhaled corticosteroid.